Serological evidence of SARS-CoV-2 exposure in marine mammals in the United States between 2020 and 2025 - Idrissa Nonmon Sanogo; Wendy B. Puryear; Alexa F. Simulynas; Robert DiGiovanni; Caroline E. Goertz; Natalie Hunter; Kathy Burek Huntington; Natalie Rouse; Rosemary E. Seton; Nicole E. Hunter; Kim Schulam; Stephen J. St. Pierre; et al. (PLoS ONE, 2026)
Natural infections of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have been documented in over 60 animal species, some distantly related. Several marine mammals have been predicted as highly susceptible to SARS-CoV-2 infection based on the homology of their ACE2 receptors to those of humans. To assess potential exposure of marine mammals to SARS-CoV-2, we conducted an opportunistic survey from 2020 to 2025 and tested 1,808 swabs and 378 serum samples from 21 marine mammal species in the United States. All the swabs tested by RT-qPCR were negative, indicating the absence of active infection. A low level of SARS-CoV-2 neutralizing antibodies was detected in three pinniped species, including Phoca vitulina (harbor seal, 13.6%, 95% CI: 5.2–27.4%), Zalophus californianus (California sea lion, 7%, 95% CI: 1.9–17.0%), and Halichoerus grypus (grey seal, 3.7%, 95% CI: 0.5–12.7%). These findings represent the first serological evidence of SARS-CoV-2 exposure in marine mammals in the United States, highlighting the need for continued monitoring of these populations and further research on SARS-CoV-2 transmission dynamics in wildlife.